2010
DOI: 10.1007/978-3-642-16358-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Energy Efficiency Improvements in Manufacturing Processes

Abstract: Global warming, rising energy prices and increasing awareness of "green" customers have brought energy efficient manufacturing on top of the agenda of governments as well as of industrial companies. The industrial sector still accounts for about 33% of the final energy consumption. This paper will contribute to a more energy efficient manufacturing by demonstrating how energy efficiency can be integrated into different levels of decision-making in companies. The paper will present methods for measuring and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Moreover, the definition of suitable performance indicators is a basic requirement for an ICT enabled management of energy efficiency. In [28] a selection of energy efficiency KPIs can be found, which are implemented in manufacturing companies, especially in the energy-intensive industries. Two typical indicators are the energy intensity (EI) and the specific energy consumption (SEC).…”
Section: Examples For Research Areas Where Ict Acts As Enabler Of Eemmentioning
confidence: 99%
“…Moreover, the definition of suitable performance indicators is a basic requirement for an ICT enabled management of energy efficiency. In [28] a selection of energy efficiency KPIs can be found, which are implemented in manufacturing companies, especially in the energy-intensive industries. Two typical indicators are the energy intensity (EI) and the specific energy consumption (SEC).…”
Section: Examples For Research Areas Where Ict Acts As Enabler Of Eemmentioning
confidence: 99%
“…In their study conducted among the largest corporations in Sweden, Sandahl and Sjögren (2002) showed that PB is the most commonly applied capital budgeting tool in all types of industries, but is also the most frequently used in the engineering sector (90% of the studied firms stated they used the PB method). The PB method is also a commonly applied tool for the evaluation of energy efficiency investments (e.g., Harris et al, 2000;Sandberg and Söderström, 2003;Bunse et al, 2009). However, firms, in particular larger firms, occasionally complement their evaluation methods with NPV and IRR, for instance (Sandahl and Sjögren, 2003).…”
Section: Economic Evaluation Of Energy Efficiency Investmentsmentioning
confidence: 99%
“…Monitoring and simulation are seen as essential elements of energy management [1]. Key Performance Indicators (KPIs) are developed to evaluate if changes in the process for increasing energy efficiency have a verifiable benefit [13]. Their monitoring supports assessment of optimization potentials and visualization of benefits from improvement measures.…”
Section: Top-down Perspective: Energy Management Systemsmentioning
confidence: 99%